Seasonal ice-covered lake surface likely caused the spatial heterogeneity of aeolian sediment grain-size in the source region of Yellow River, northeastern Tibetan Plateau, China - Hu, Guangyin; Hu, Jingjing; Dong, Zhibao; Yang, Linhai (Frontiers in Earth Science, 2023)
The source region of Yellow River (SRYR) is located in the northeastern Tibetan Plateau (TP). Aeolian sediments collected in this region shows great spatial difference of the mean grain sizes (mainly varying between 70 and 230 μm). The end-member analysis provides a greater chance of resolving aeolian sediment sources since it can quantitatively separate the particle size components of various sedimentary dynamic processes and sources in the sediment. In this study, parametric EMMA is applied to study the provenance tracing of aeolian sediment. Aeolian processes were analyzed by separating and extracting the grain size end-members of nine sections from the SRYR. Four statistical end-members were classified from the grain size distribution. Among these, the clay-dominated EM1 (modal grain size is 8.9 μm) shows background dust produced by vertical airflow transport of high-altitude westerly circulation. EM2 (modal grain size is 79.5 μm) and EM3 (modal grain size is 141.6μm), formed by coarse silty sand and fine sand, show a reciprocal relationship in the particle size distribution. They may represent medium distance transport at a regional scale due to the low-altitude wind system. EM4 (modal grain size is 251.8 μm), which consists of fine to medium sands, representing the leapfrog component of the proximal material transport. Due to the variation of material source and depositional environment, the content ratio of each terminal element shows significant variability in different profiles and different layers. In particular, in sections 7 and 8, these two sedimentary sequences have high EM2 and EM3 fractions and very low EM4 content at all depths. Based on comprehensive analysis of aeolian sediment grain-size, phenology of ice lake, wind regime and remote sensing images, we suggest that the fine aeolian sediments (sections 7 and 8) on the downwind shore of Ngoring Lake likely transported from the upwind shore, which were blown across the ice-covered lake surface by prevailing west wind in winter and spring, but the coarse sediments could be trapped by ice cracks. It is concluded that the aeolian sediment transport on frozen lakes may lead to the spatial heterogeneity of aeolian sediment grain-size in the SRYR.